2020
DOI: 10.13152/ijrvet.7.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Building a skilled workforce: Public discourses on vocational education in Thailand

Abstract: Context: Thailand is now facing skilled labour shortages, which has prevented the country from achieving significant economic progress. This paper examines Thailand’s vocational education policy discourses from 1992 to 2014 and how such policies were discussed to build the country’s skilled labour force.Approach:This study utilised a qualitative approach, using documentation analysis as a key research method. We also used data triangulation and thematic analysis to categorise the public discourses. In order to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Of course, in doing so, vocational workers have been emphasized for greater preparation for entering the workforce (Fuller, 2015;Hanushek et al, 2017;Jacobs & Hawley, 2009) Over the years, Thailand has improved access to education for young people to reduce disparities, but it was found that there are still problems with a gap between skills and labor requirements (International Labour Organization [ILO], 2019). This includes a shortage of professional skilled workers that meet the industry's needs (Chalapati & Chalapati, 2020). This challenge influenced the mechanisms for creating effective training courses to improve the quality of education (Japan International Cooperation Agency [JICA], 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of course, in doing so, vocational workers have been emphasized for greater preparation for entering the workforce (Fuller, 2015;Hanushek et al, 2017;Jacobs & Hawley, 2009) Over the years, Thailand has improved access to education for young people to reduce disparities, but it was found that there are still problems with a gap between skills and labor requirements (International Labour Organization [ILO], 2019). This includes a shortage of professional skilled workers that meet the industry's needs (Chalapati & Chalapati, 2020). This challenge influenced the mechanisms for creating effective training courses to improve the quality of education (Japan International Cooperation Agency [JICA], 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research offers insight into the design development and implementation of online design thinking-based entrepreneurship courses at the vocational college level. Vocational education has been recognized as an effective tool to reduce unemployment and increase the firms' productivity, which is necessary for the country's development (Chalapati & Chalapati, 2020). This uncertain era requires students in vocational education to develop entrepreneurship skills and Woraphiphat and Roopsuwankun Journal of Innovation and Entrepreneurship (2023) 12:10 innovation to promote the country's economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Thailand, which is a developing country situated in Southeast Asia, the mechatronics and robotic programme of the Thai VET has become essential to the procurement of the manpower necessary for Thailand 4.0's technology-driven economy ambitions (Chomsuwan et al, 2020). However, a thorough policy discourse analysis has indicated that there has been a shortage in vocationally skilled workers in Thailand despite various policies aiming to increase the number of skilled labour workforce have been implemented over the past few decades (Chalapati and Chalapati, 2020). Our study further emphasises that the quality of vocational workers is also an important concern, because even if the number of vocational students can be increased, the problem of a skilled workforce shortage is likely to remain if those students do not have adequate relevant skills and knowledge required to work in their occupations.…”
Section: Introductionmentioning
confidence: 99%